Development of Soviet Ideological Censorship in Lithuania (1964–1989) - Skorupskas, Andrius (Genocidas ir rezistencija, 2025)
The development of Soviet ideological censorship in Lithuania in 1964–1989 can objectively be divided into three periods:1) 1964–1972: The period of the legacy of the ideological censorship of Khrushchev, and the gradual entrenchment of the new bureaucratic regime of Brezhnev; the impression of the "loosened grip" and the possibility to use this juncture. The 1972 events in Kaunas induced the Soviet authorities to strengthen the influence of the ideological censorship.2) 1972–1985: The time of the constant pressure of ideological censorship, the reckless evasion of even minor alternatives to public-cultural manifestations, which could contradict the official ideology. 1983–1984: This is the stage of the last intensification of ideological censorship. Strict measures were applied to escape the "stagnation" quagmire and the increasingly obvious discontent of the society. In 1985, political changes affected the whole USSR: the aim was publicity: the society was becoming free.Considering the aspect chosen in this article, the last period is likely to be the most relevant. Only under the conditions of so-called "mature socialism" did the Soviet ideological censorship acquire all possible shapes: from simply sanitizing the manuscripts and victimizing the author emotionally, to ideologically sterilizing the entire cultural sphere. The society was deprived of the right to access reliable information. The censors would often explain their actions by referring to violations of the norms of the "List" which had been sent from Moscow. Yet, the "qualifications" of the Lithuanian SSRGlavlit were not always sufficient, especially in an emergency (1972) or when the system was tightened (1983–1984). At that time, the local KGB was involved in the work of ideological censorship as well and would constantly control the processes, which were taking place in the spheres of cultural life and public opinion. The latter was rather the "supplement" of repression and control with almost absolute authority for emotional or even physical terror.3) 1985–1989: The period of ideological crisis. The censorship was growing weaker, though it attempted for some time to adapt, until the Revival when it completely lost its meaning.It can be asserted that the intensity of the Soviet ideological censorship depended directly on the very spirit of the regime. At the end of Khrushchev's rule, one still could sense remnants of the "Thaw": there was also some effect resulting from the anti-cultural campaigns launched by Nikita Khrushchev. In the period of Brezhnev's regime, the "institutional-team administration" of public life became prevalent; there was constant restraint and no tendencies for change could be observed. During their tenure, Yuri Andropov and Konstantin Chernenko strengthened discipline; the censorship flourished. Great changes took place only during Gorbachev's perestroika. While analysing the development and the characteristics of Soviet censorship in Lithuania, it is essential to consider the context of the processes, which developed in the USSR, since the latter was the commanding force implementing ideological censorship.
Keywords: art; culture; Soviet culture; cenzorship; communist ideology